Heat Shock Factor Hsf1 Cooperates with ErbB2 (Her2/Neu) Protein to Promote Mammary Tumorigenesis and Metastasis - Xi, Caixia (American Society for Biochemistry and Molecular Biology, 2012)
ErbB2/Neu oncogene is overexpressed in 25% of invasive/metastatic breast cancers. We have found that deletion of heat shock factor Hsf1 in mice overexpressing ErbB2/Neu significantly reduces mammary tumorigenesis and metastasis. Hsf1(+/−)ErbB2/Neu(+) tumors exhibit reduced cellular proliferative and invasive properties associated with reduced activated ERK1/2 and reduced epithelial-mesenchymal transition (EMT). Hsf1(+/+)Neu(+) mammary epithelial cells exposed to TGFβ show high levels of ERK1/2 activity and EMT; this is associated with reduced expression of E-cadherin and increased expression of Slug and vimentin, a mesenchymal marker. In contrast, Hsf1(−/−)Neu(+) or Hsf1(+/+)Neu(+) cells do not exhibit activated ERK1/2 and show reduced EMT in the presence of TGFβ. The ineffective activation of the RAS/RAF/MEK/ERK1/2 signaling pathway in cells with reduced levels of HSF1 is due to the low levels of HSP90 in complex with RAF1 that are required for RAF1 stability and maturation. These results indicate a powerful inhibitory effect conferred by HSF1 downstream target genes in the inhibition of ErbB2-induced breast cancers in the absence of the Hsf1 gene.